2021
DOI: 10.1371/journal.pone.0241652
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of a mild isolate of papaya ringspot virus type-P (PRSV-P) and assessment of its cross-protection potential under greenhouse and field conditions

Abstract: A mild isolate of Papaya ringspot virus type-P, abbreviated as PRSV-mild, from Ecuador was sequenced and characterized. The most distinguishing symptom induced by PRSV-mild was gray powder-like leaf patches radiating from secondary veins. In greenhouse experiments, PRSV-mild did not confer durable protection against a severe isolate of the virus (PRSV-sev), obtained from the same field. Furthermore, isolate specific detection in mixed-infected plants showed that PRSV-sev becomes dominant in infections, renderi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…Indeed, it has been demonstrated that superinfection exclusion is dependent on the genetic proximity between the protective strain and its challengers [ 36 ]. Strain-specific protection was clearly observed for CTV [ 91 , 92 ], ZYMV [ 43 , 93 ], and papaya ringspot virus (PRSV) [ 48 , 94 ]. In this context, the four mild symptomatic vines that host potentially mild GFLV isolates that were identified in our study might be of great interest for cross-protection, as they belong not only to divergent phylogenetic lineages but also to the two most represented clades of GFLV ORF1 and ORF2 (sequences clades I.A, I.B, II.A and II.B), and were detected in both sites except for clade I.A.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that superinfection exclusion is dependent on the genetic proximity between the protective strain and its challengers [ 36 ]. Strain-specific protection was clearly observed for CTV [ 91 , 92 ], ZYMV [ 43 , 93 ], and papaya ringspot virus (PRSV) [ 48 , 94 ]. In this context, the four mild symptomatic vines that host potentially mild GFLV isolates that were identified in our study might be of great interest for cross-protection, as they belong not only to divergent phylogenetic lineages but also to the two most represented clades of GFLV ORF1 and ORF2 (sequences clades I.A, I.B, II.A and II.B), and were detected in both sites except for clade I.A.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings of higher recombination rates in Asian specifically Chinese and Indian isolates were put forward in a recent report [ 25 ]. As our recombination analysis comprised of all the recently sequenced genomes thereby it is noteworthy to mention the detected recombination in lately sequenced severe PRSV-P isolate from Ecuador (South America) MH974110 [ 68 ]. However, the Table 4 states only the recombination events of PRSV-PK.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of symptoms on papaya plants inoculated with isolates from Cibinong is symptoms of mottle leaves evenly distributed, vein clearing is evenly distributed, pale leaf colour and wilted, and transparent or typical oily streaks evenly distributed throughout the stem and even seen on the lower lamina of the leaves (Figure 1). According to [12] that mechanical inoculation of severe strains of PRSV to papaya plants caused vein clearing, typical oily streaks on the stems and stunting while the manifestation of symptoms by weak strains only resulted in subtle grey powder-like patches, which radiated from the secondary veins of young fully developed leaves. From this description, the three isolates in this test are classified as virulent strains because they cause symptoms of uniform vein clearing, mottle and oily streaks on the stem.…”
Section: Symptom Of Each Prsv Isolate In Reservoir Plantsmentioning
confidence: 99%